ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHIKINERJA KEUANGAN PERUSAHAAN MANUFAKTUR TERDAFTAR DI BEI PERIODE 2019-2021 - Totok Susilo Pamuji Nugroho; Yohana Delvas Prahesti (Universitas Merdeka Madiun, 2023)
The purpose of this study is to analyze the effect of Liquidity, Solvency, and Profitability ratios on Financial Performance in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2020 period in the Food & Baverage sector. The sampling technique in this study used the purpose sampling method which resulted in 19 companies. Hypothesis testing using multiple linear regression analysis. The results of this study indicate that the ratio of Liquidity, Solvency, and Profitability has a positive and significant effect on financial performance. The analysis technique of this research uses multiple linear analysis with a significance level of 0.05. Based on the results of the study stated that the liquidity ratio had a significant effect on financial performance of 0.000 <0.05. While the solvency ratio has a significant effect on financial performance of 0.000 <0.05, and the profitability ratio has a significant effect on financial performance of 0.003 <0.05. Keywords : Liquidity Ratio, Solvency, Profitability, and Financial Performance